2016
DOI: 10.1111/bjd.14798
|View full text |Cite
|
Sign up to set email alerts
|

Comparing preferences for outcomes of psoriasis treatments among patients and dermatologists in the U.K.: results from a discrete-choice experiment

Abstract: Estimates of patients' risk tolerance for serious side-effects indicate that patients valued psoriasis symptom control highly and suggest that psoriasis symptoms have a significant effect on patients' quality of life. In light of research showing increased treatment satisfaction and improved treatment adherence among patients who receive therapies that are consistent with their preferences, our findings suggest that greater communication between dermatologists and patients about risk tolerance could help impro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 37 publications
2
21
0
Order By: Relevance
“…However, the DCE did not take process attributes into account, and the outcome attributes do not reflect the features of biologicals. More recently, the preferences of 174 patients with psoriasis and 100 dermatologists for efficacy and safety of biologicals were compared using DCE (26). The attributes considered were location and coverage of the plaques, improvement in severity, and risks of tuberculosis, serious infections and lymphoma.…”
Section: Discussionmentioning
confidence: 99%
“…However, the DCE did not take process attributes into account, and the outcome attributes do not reflect the features of biologicals. More recently, the preferences of 174 patients with psoriasis and 100 dermatologists for efficacy and safety of biologicals were compared using DCE (26). The attributes considered were location and coverage of the plaques, improvement in severity, and risks of tuberculosis, serious infections and lymphoma.…”
Section: Discussionmentioning
confidence: 99%
“…Prior research indicated that shared decision-making between physicians and patients led to greater levels of satisfaction with treatment and ultimately better health outcomes, particularly for chronic conditions such as psoriasis [ 14 17 , 22 ]. Knowing that physicians and patients may have similar preferences for attributes of treatment could enable patients to more readily voice their opinion and be an active participant in treatment decision-making.…”
Section: Discussionmentioning
confidence: 99%
“…ustekinumab) were women and the working population, while our analysis found that these preferences were not met. A recent comparison of dermatologist and patient preferences has highlighted the potential for improved patient care following better communication between these groups . There may be an important role to play for shared decision making and the use of patient decision aids in the context of dermatology …”
Section: Discussionmentioning
confidence: 99%
“…A recent comparison of dermatologist and patient preferences has highlighted the potential for improved patient care following better communication between these groups. 32 There may be an important role to play for shared decision making and the use of patient decision aids in the context of dermatology. 33 The importance of understanding the drivers of treatment choice is emphasized by the increasing complexity for clinicians and patients in selecting a first-line biologic, with a larger number of candidate drugs becoming available.…”
Section: Discussionmentioning
confidence: 99%